2018
DOI: 10.1186/s12888-018-1820-x
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral activation versus treatment as usual in naturalistic sample of psychiatric patients with depressive symptoms: a benchmark controlled trial

Abstract: BackgroundMore systematic use of evidence-based brief therapies is needed in the treatment of depression within psychiatric care. The aim of this study was to explore the impact of behavioral activation therapy (BA) for patients with depressive symptoms in a routine clinical setting of secondary psychiatric care.MethodsThe BA-treated intervention group (n = 242) comprised patients with depressive symptoms (Beck Depression Inventory (BDI) score ≥ 17 at baseline). The control group (n = 205) patients received tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
(23 reference statements)
0
9
0
Order By: Relevance
“…However, the clinical effectiveness study ODS recently showed that BA were beneficial in comparison with treatment-as-usual in regard to patient outcomes (33). It is also appropriate to note that there are several other factors, many of them complex or multidimensional, which are influential in implementation programmes but not controlled for in the present study.…”
Section: Limitationsmentioning
confidence: 83%
“…However, the clinical effectiveness study ODS recently showed that BA were beneficial in comparison with treatment-as-usual in regard to patient outcomes (33). It is also appropriate to note that there are several other factors, many of them complex or multidimensional, which are influential in implementation programmes but not controlled for in the present study.…”
Section: Limitationsmentioning
confidence: 83%
“…The method has been designated an empirically validated treatment (e.g., NICE, ), and several meta‐analyses have demonstrated BA to be an effective treatment for depression (e.g., Cuijpers, Karyotaki, de Wit, & Ebert, ; Ekers et al, ). BA is easy to administer (see Richards et al, ) and efficacious within many diverse patient populations (e.g., Alexopoulos et al, ; Folke et al, ; Luoto et al, ; Ryba, Lejuez, & Hopko, ; Xie et al, ) in individual as well as in group treatment formats (Ekers et al, ). Given its parsimonious and straightforward rationale, BA is considered highly suitable for large scale dissemination (see Richards et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…A quantitative evaluation of the ODS-I showed that a third of the target group of the programme were active adopters of MI and BA (20). The ODS was intended to study the effectiveness of MI and BA in a naturalistic setting and the results were positive (21).…”
Section: Contributions To the Literaturementioning
confidence: 99%